Transitioning from practicing teacher to teacher leader: a case study. Issue 1 (1st January 2019) - Gerstenschlager, Natasha E.; Barlow, Angela T.
ABSTRACT: Given US students' lack of international competitiveness in mathematics and science, many states have adopted the Common Core State Standards for Mathematics (CCSSM). To help ensure that the Standards for Mathematical Practice within the CCSSM and effective teaching practices are implemented appropriately, many teachers are emerging as teacher leaders with the intent of supporting teachers with this implementation. Unfortunately, not all of these teachers are necessarily prepared in the field of teacher leadership. Recognizing the importance of having well-prepared teacher leaders, this article describes the case of Ms. Hodges, as she transitioned from mathematics teacher to teacher leader. Data revealed that several factors affected Ms. Hodges' transition, some positively and others negatively. These results as well as implications for teacher leader development are provided.